In-situ monitoring and ex-situ elasticity mapping of laser induced metal melting pool using ultrasound: Numerical and experimental approaches. (November 2021) - Yang, Teng; Jin, Yuqi; Squires, Brian; Choi, Tae-Youl; Dahotre, Narendra B.; Neogi, Arup
Abstract: This study presents novel in-situ monitoring of the melting pool behavior and ex-situ inspection of the heat-affected softening in gallium metal using an ultrasonic technique. In the laser welding and laser melting additive manufacturing process, understanding the melting pool's behavior is necessary but challenging. Optical, thermal, and radiational imaging methods provide valuable information but are limited due to the lack of depth and material properties information. An ultrasonic time of flight measurement monitoring technique is numerically and experimentally used to study the behavior of laser-induced melting pools, including phase transition, pool initialization and growth, and solidification in real-time. Besides, a dynamic bulk modulus elastography scan was demonstrated to visualize the laser-heating induced mechanical property reduction as an ex-situ inspection process which can be an in-situ process in the future. The laser softened area had a drop in the elasticity resembling a melt pool's shape. With the continuous development, the unique technique would be suitable and helpful to be used as a diagnostic tool to monitor laser welding, laser melting-based additive manufacturing, and other melt-solidify processing systems.